2009
DOI: 10.3354/dao02129
|View full text |Cite
|
Sign up to set email alerts
|

Comparative experimental transmission of cardiomyopathy syndrome (CMS) in Atlantic salmon Salmo salar

Abstract: Cardiomyopathy syndrome (CMS) has been recorded in wild and farmed Atlantic salmon Salmo salar. Characteristic heart lesions primarily involving the myocardium are reported in natural outbreaks with associated mortality. To date, no experimental trials have reproduced these lesions in the laboratory. The present study reports on the first successful experimental transmission of CMS in Atlantic salmon in Scotland, with full development of the histological lesions that are described for the syndrome. Tissue homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
(60 reference statements)
0
30
0
Order By: Relevance
“…Several studies have suggested that HSMI and CMS are associated with viruses , 2006, Vågenes et al 1999, Nylund 2001, Kongtorp et al 2004a, Bruno & Noguera 2009, Fritsvold et al 2009, Palacios et al 2010. However, using homogenates containing these viruses in challenge experiments will not reproduce all the signs of these diseases and the mortality observed in field outbreaks (A. Nylund pers.…”
Section: Heart and Skeletal Muscle Inflammation And Cardiomyopathy Symentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have suggested that HSMI and CMS are associated with viruses , 2006, Vågenes et al 1999, Nylund 2001, Kongtorp et al 2004a, Bruno & Noguera 2009, Fritsvold et al 2009, Palacios et al 2010. However, using homogenates containing these viruses in challenge experiments will not reproduce all the signs of these diseases and the mortality observed in field outbreaks (A. Nylund pers.…”
Section: Heart and Skeletal Muscle Inflammation And Cardiomyopathy Symentioning
confidence: 99%
“…during the second year at sea (Bruno & Noguera 2009, Fritsvold et al 2009). It is believed that CMS is caused by viruses , Vå-genes et al 1999, Nylund 2001, Bruno & Noguera 2009, Fritsvold et al 2009. CMS is diagnosed on characteristic changes in the atrium and the spongiosum of the ventricle of the heart (Fig.…”
Section: Heart and Skeletal Muscle Inflammation And Cardiomyopathy Symentioning
confidence: 99%
See 2 more Smart Citations
“…This was based on the presence of eosinophilic inclusions in nuclei of myocardial fibres in the vicinity of degenerated areas. Experimental transmission studies have supported this hypothesis (Bruno & Noguera 2009, Fritsvold et al 2009, and in 2010 a doublestranded RNA virus tentatively of the Totiviridae family was described as the causative agent of CMS (Løvoll et al 2010, Haugland et al 2011.…”
Section: Introductionmentioning
confidence: 81%